Advancing Orthodontic Aesthetics: Exploring the Potential of Injectable Composite Resin Techniques for Enhanced Smile Transformations - Davide Spadoni; Cristina Valeri; Vincenzo Quinzi; Ute Schneider Moser; Giuseppe Marzo (Dentistry Journal)
Background/Objectives: The injection moulding technique (IMT) is a minimally invasive restorative treatment. This technique enables the application of thin, flowable composite layers into a stable, transparent silicone index that serves as a mould. Due to the fluid properties of the composite, it efficiently fills the silicone tray and seamlessly integrates with the tooth structure, often obviating tooth preparation and preserving overall tooth integrity. The procedure employs the etch-and-rinse protocol and is highly reproducible. Minimally invasive restorative techniques are particularly relevant following orthodontic treatment, where minor tooth adjustments are often required to achieve optimal aesthetics and function. Integrating orthodontic and restorative treatments is pivotal for long-term success, especially in complex interdisciplinary cases. Methods: This retrospective study describes the application of conservative restoration using the IMT in two pediatric patients (12.6 years old and 12.3 years old) to restore maxillary lateral incisors before and after orthodontic treatment. The technique provides a viable option for temporary composite restorations until the patients are suitable candidates for permanent all-ceramic veneers. Results: The injectable technique is ideal for minimal diastemas, small interdental spaces, or retruded teeth. The cases presented, involving irregular tooth sizes and morphologies, demonstrate the suitability of the IMT in scenarios requiring an additive approach. This technique effectively addresses such irregularities without necessitating invasive preparation. Conclusions: The IMT is a valuable tool for pediatric patients undergoing orthodontic treatment, both at its initiation and completion. The technique assists orthodontists in finalising treatment by addressing Bolton index discrepancies and correcting tooth shape anomalies. Additionally, a digital workflow reduces clinical sessions, as thermo-printed retainers can be delivered during the same appointment as the IMT, providing economic and organisational benefits. This approach underscores the utility of the IMT in enhancing treatment efficiency and outcomes in orthodontic–restorative care.